2022
DOI: 10.1080/20008198.2022.2087979
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for posttraumatic stress and posttraumatic growth in parents of children with intellectual and developmental disorders

Abstract: Background: Parents of children with intellectual and developmental disorders often experience potentially traumatic events while caring for their children. Heightened posttraumatic stress (PTS) and posttraumatic growth (PTG) have been found in this population. Objective: We aimed to explore risk and protective factors for their PTS and PTG. Method: A cross-sectional study was conducted with 385 parents (average age M = 43.14 years, SD = 7.40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
0
3
0
1
Order By: Relevance
“…This can be used to develop effective methods for the prevention of PTSD in nonmedical professionals. Also, based on the analyzed publications, it was found that the support of the family and social environment during the action of the traumatic stress factor and throughout life is of crucial importance for promoting an individual's resilience (Xiong, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This can be used to develop effective methods for the prevention of PTSD in nonmedical professionals. Also, based on the analyzed publications, it was found that the support of the family and social environment during the action of the traumatic stress factor and throughout life is of crucial importance for promoting an individual's resilience (Xiong, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…[ [10][11][12]. There remains a gap in the evidence base of post-traumatic growth of parents with children with DMD.…”
Section: Discussionmentioning
confidence: 99%
“…O mesmo estudo ainda infere que o apoio social a esses indivíduos é um fator de proteção para os cuidadores. Com isso, pode destacar que um dos obstáculos para melhora da qualidade de vida dos cuidadores é exatamente o acesso precário aos serviços de apoio à saúde mental (Xiong et al, 2022;(Kurowska;Kózka;Majda, 2021). Contribuciones a Las Ciencias Sociales, São José dos Pinhais, v.17, n.6, p. 01-23, 2024…”
Section: Categoria 3 -Estratégias De Enfrentamentounclassified